Beta-2-microglobulin mutations are linked to a distinct metastatic pattern and a favorable outcome in microsatellite-unstable stage IV gastrointestinal cancers - Busch, Elena; Ahadova, Aysel; Jäger, Dirk; Knebel Doeberitz, Magnus von; Haag, Georg Martin; Kloor, Matthias (Frontiers in oncology, 2021)
Immune checkpoint blockade (ICB) shows remarkable clinical effects in patients with metastatic microsatellite-unstable (MSI) cancer. However, markers identifying potential non-responders are missing. We examined the prevalence of Beta-2-microglobulin (B2M) mutations, a common immune evasion mechanism, in stage IV MSI gastrointestinal cancer and its influence on metastatic pattern and patients’ survival under ICB. Twenty-five patients with metastatic, MSI gastrointestinal adenocarcinoma were included. Eighteen patients underwent ICB with pembrolizumab and one patient with nivolumab/ipilimumab. Sequencing was performed to determine B2M mutation status. B2M mutations and loss of B2M expression were detected in 6 out of 25 stage IV MSI cancers. B2M mutations were strongly associated with exclusively peritoneal metastasis (p=0.0312). However, no significant differences in therapy response (25% vs. 46.6%, p>0.99) and survival (median PFS: 19.5 vs 33.0 months, p=0.74; median OS 39 months vs. not reached, p>0.99) were observed between B2M-mutant and B2M-wild type tumor patients. Among metastatic MSI GI cancers, B2M-mutant tumors represent a biologically distinct disease with distinct metastatic patterns. To assess ICB response in B2M-mutant MSI cancer patients, future studies need to account for the fact that baseline survival of patients with B2M-mutant MSI cancer may be longer than of patients with B2M-wild type MSI cancer.
Gesehen am 06.07.2021